2007
DOI: 10.1371/journal.pgen.0030214
|View full text |Cite
|
Sign up to set email alerts
|

Rrp1b, a New Candidate Susceptibility Gene for Breast Cancer Progression and Metastasis

Abstract: A novel candidate metastasis modifier, ribosomal RNA processing 1 homolog B (Rrp1b), was identified through two independent approaches. First, yeast two-hybrid, immunoprecipitation, and functional assays demonstrated a physical and functional interaction between Rrp1b and the previous identified metastasis modifier Sipa1. In parallel, using mouse and human metastasis gene expression data it was observed that extracellular matrix (ECM) genes are common components of metastasis predictive signatures, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
92
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 38 publications
(64 reference statements)
4
92
0
Order By: Relevance
“…Identification of RRP1B as a promoter of apoptosis may also suggest an explanation for the observation of higher survival in breast cancers with an expression profile driven by high RRP1B expression (23,68). RRP1B may be an important factor in apoptotic response to genotoxic agents and aberrant proliferation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of RRP1B as a promoter of apoptosis may also suggest an explanation for the observation of higher survival in breast cancers with an expression profile driven by high RRP1B expression (23,68). RRP1B may be an important factor in apoptotic response to genotoxic agents and aberrant proliferation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…RRP1B is related to RRP1 (ribosomal RNA processing 1), a protein involved in ribosomal biogenesis localized to the nucleolus (19 -22). Recent data have shown that RRP1B is involved in suppression of metastasis, and a gene expression profile obtained following its overexpression predicted survival in breast cancers (23). However, the mechanism of how RRP1B reduces tumor burden remains unclear.…”
mentioning
confidence: 99%
“…TGFA, a gene known to be regulated by E2 (Fontana et al 1992) and overexpressed in endometrial cancer (Niikura et al 1996), is up-regulated by E2, GEN, and BPA. RRP1B, up-regulated only by E2, is thought to play a role in ribosomal RNA processing and may be involved in metastatic potential (Crawford et al 2007). SLC22A5, a carnitine transporter associated with autoimmune diseases (Peltekova et al 2004;Santiago et al 2006), is significantly up-regulated by E2 only but shows similar changes after GEN and BPA treatment.…”
Section: à4mentioning
confidence: 99%
“…To explore the detailed mechanisms of influenza virus transcription, we focused on the candidate host proteins with potential functions in the regulation of cellular transcription or RNA processing, since influenza virus transcription relies on host transcription (13). From the list, we focused on the rRNA processing 1 homolog B (RRP1B) gene, which was previously identified as a susceptibility gene for breast cancer progression and metastasis (14). RRP1B is a multifunctional protein that has been implicated in several biological processes.…”
mentioning
confidence: 99%